OVUM PICK UP (LOPU) IN SANTA INES SHEEP: LEARNING CURVE AND TECHNICAL DETAILS Aspiração folicular ovariana em ovelhas da raça Santa Inês: curva do aprendizado e detalhes técnicos - Maia Teixeira, Pedro Paulo; Padilha, Luciana Cristina; do Socorro Lima da Silva, Alanna; Farias Pereira da Câmara Barros, Felipe; Nassar Coutinho, Leandro; Franco Oliveira, Maria Emília; Ferguson Motheo, Tathiana; Machado Silva, Marco Augusto; Niderauer Flôres, Fabiola; Seudo Lopes, Maristela de Cássia; et al. (Revista Acadêmica Ciência Animal, 2013)
The aim of the current study was to assess the efficacy, the learning curve and associated technical difficulties oflaparoscopic ovum pick-up (LOPU) in sheep. Ten ovum pick-up sessions were performed in six Santa Ines sheep during a cycle of 7-day intervals, totaling 60 laparoscopic procedures. The sheep were managed for synchronizationof the estrous cycle. The laparoscopic approach was carried out using three ports. The number of follicles viewed, aspirated follicles and oocytes recovered were 13.32 ± 2.8, 11.37 ± 2.8 and 6.36 ± 2.0, respectively. Total operation time was used to assess the learning curve among 10 laparoscopic sessions. Mean surgical time was relatively short (26.75 ± 9.6 minutes). Surgical time decreased from the first session on (P < 0.05). LOPU was demonstrated to be a procedure with little intercurrence and with a short learning curve. Others studies regarding this technique should be performed to minimize possible complications and enabling its use in the field